Agricultural Information, Indigenous Knowledge and Development Communication Strategies among Women in Ijaye Community (2004)
This study examines the impact of indigenous development communication strategies on the utilization of Agricultural information among women for rural development. Ijaye community of Akinyele local government area of Oyo State was used as case study. It also investigated the channels of communication adopted by development workers with reference to indigenous knowledge. The data for the study were collected through the questionnaire; focus group discussion, oral interviews and existing comparative literature. It was revealed in this study that indigenous channels and local strategies have received the desired attention in the development communication process. From the study findings reveal that the strategies adopted in a communication encounter, significantly affects the understanding and utilization of the message. The more familiar the strategy/channels, the more result yielding. Some of the indigenous strategies and channels like, local associations, local festivals, songs, folktales etc can he successfully adopted in communicating exogenous information, new idea and practices to the people. If this exogenous information is therefore packaged in format rooted in the culture of the audience, they will have a better chance.